Spray flash evaporator for low-temperature saline water desalination application. (20th November 2007) - Paden, J. Justin Robert; Tewari, P.K.; Venkatram, D.; Barnabas, D.
A new spray-type flash evaporator is suggested for the application of saline water desalination. The flash evaporator is 1000 mm in height and 1200 mm in diameter, with a water injection arrangement inside. The evaporator design is based on experiments conducted at vacuum pressures between 10 and 18 mm of Hg, and at saline feed water temperatures between 26?C and 32?C. The saline water is injected into a vapouriser through a pair of high-flow swirl injectors with a nominal flow rate of 1.5 litre/sec. per jet and the distance between the injectors is taken as 200 mm for design. The influence of the different thermal, hydrodynamic and geometric parameters on the evaporator performances was investigated. The results obtained are presented, which prove the validity of the proposed system.